2019
DOI: 10.1111/add.14645
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous progesterone for smoking cessation in men and women: a pilot double‐blind, placebo‐controlled randomized clinical trial

Abstract: Background and Aims In some clinical studies men and women have been found to differ in their ability to quit smoking, perhaps as a result of progesterone. The primary aim of this study was to provide a preliminary test of whether progesterone (PRO), compared with placebo (PBO), was more effective for smoking cessation in men and women. Design Pilot double‐blind, placebo‐controlled randomized clinical trial. Setting Minneapolis/St Paul metro area, Minnesota, USA. Participants A total of 216 participants were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Tosun and colleagues (2019) found that progesterone aids smoking cessation among women smokers. Twice‐daily exogenous administration of 200 mg oral micronized progesterone increased rates of abstinence at 1 month after the initiation of treatment and delayed relapse in women, but not men . These results add to a growing literature identifying that the administration of exogenous progesterone may serve as a novel intervention for substance use disorders, including tobacco use .…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…Tosun and colleagues (2019) found that progesterone aids smoking cessation among women smokers. Twice‐daily exogenous administration of 200 mg oral micronized progesterone increased rates of abstinence at 1 month after the initiation of treatment and delayed relapse in women, but not men . These results add to a growing literature identifying that the administration of exogenous progesterone may serve as a novel intervention for substance use disorders, including tobacco use .…”
mentioning
confidence: 59%
“…In their study, participants were maintained on stable levels of progesterone (ranging from 3 to 25 ng/ml), similar to levels observed during the mid‐luteal phase of the menstrual cycle when naturally occurring progesterone levels are at their highest and estradiol levels are low. While repeated assessments of ovarian hormone levels were not reported in Tosun et al , it is possible that the administration of exogenous progesterone lead to an absence of dynamic hormone change (while maintaining a high progesterone to estradiol ratio), and this may be beneficial for cessation outcomes among women smokers .…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…
Commentary on Tosun et al (2019): Dynamic changes in sex hormones and smoking cessation There is growing evidence suggesting that exogenous progesterone may improve smoking cessation outcomes among women. We hypothesize that exogenous progesterone administration can result in stable progesterone levels, and that it is the absence of dynamic hormone change that may lead to improved smoking cessation outcomes.
…”
mentioning
confidence: 99%